Law of trade unions - "Sethi, R. B." (Allahabad, 1959)
Containing illuminating expositions of the law, practice and procedure with up-to-date case-law throwing a flood of light on all aspects of the subject, explaining the scheme of the Act, objective of the Trade Unions and the ways to achieve them, dealing with collective action, legal protection to the registered Unions against civil and criminal actions, strikes, slow-down and picketing, trade disputes, trade union agreements and various Appendices, viz. Central Trade Union Regulation, Extracts from Labour Investigation (Main) Report-Industrial Disputes Act, Industrial Employment (Standing Orders) Act and Rules, Extracts from Railway Act-Indian Penal Code, Working Journalists (Conditions of Service) and Miscellaneous Provisions Act, Trade Union Regulations of Bombay, U P., Hyderabad, M. P., Assam, Madras and a model constitution of a Trade Union etc.
Keywords: Law